Flood management and control - Eken, Anıl. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2019., 2019)
The severity and frequency of flood events are expected to grow at global scale while flood events continue to lead losses and damages all around the world. Floods need a special focus to describe the risks and minimize loses or damages. In this study, main reasons of flood losses or damages researched. Solutions produced dependent on the reasons or insufficiencies determined. Also flood events that caused great damages or losses in history became a guide for preventive solutions. River basins, low lying settlements, agricultural, industrial and rural areas, cities, hillsides, high population and high precipitation areas, settlements that close to water resources are the great risk regions for flood events, and they need observations, measures, preventive approaches, flood plans, strong infrastructures, early warning systems, predictions, flood parameters, green solutions, struggle and advices as components to minimize the risks. The research aims to explain those components to prevent flood events. The flood risks of some countries and the flood risky regions or cities in the Turkey explained and predicted. Conventional flood parameters and management concepts questioned while new ones were produced. Formulation and determination of limit value of those parameters became a goal too, and also a new flood parameter structure emerged. Briefly, the contributions to the early warning system and to the elimination of complexity of flood predictions are expected as results at the end of the study.
Keywords: Floods.; Flood control.; Flood damage prevention.